Projecting the impact of a national strategy to accelerate stunting prevention in East Nusa Tenggara, Indonesia, using the Lives Saved Tool - Andriani , Helen; Arsyi, Miftahul; Sutrisno, Alphyyanto E.; Waits, Alexander; Rahmawati, Nurul D. (Narra Sains Indonesia, 2025)
Stunting remains a critical public health issue in East Nusa Tenggara (ENT), Indonesia, with prevalence rates among the highest in the country, despite national efforts to reduce its occurrence. The aim of this study was to project the impact of the 2018–2024 National Strategy to Accelerate Stunting Prevention on children under five years old in ENT, using the Lives Saved Tool. A cross-sectional approach was employed, integrating data from various sources, including the 2020 Census of Indonesia, the Global Data Lab-Area Database, the Central Bureau of Statistics Republic Indonesia, the National Socioeconomic Survey, the 2017 Indonesia Demographic and Health Survey, the 2018 Basic Health Research, and the 2021 Indonesia Nutrition Status Survey. The analysis considered three scenarios: (1) a baseline scenario reflecting ENT’s 2017 coverage, maintained through 2028; (2) a scenario assuming Indonesia achieves the Health Plan Action Stunting targets; and (3) a projection of stunting rates based on ENT-specific coverage. Under scenarios 1 and 2, the prevalence of stunting was projected to decrease from 40.04% in 2018 to 39.82% and 39.78%, respectively, by 2028, with scenario 3 reflecting a similar trend. The findings revealed a sharp increase in the number of stunting cases averted among children under five years old between 2017 and 2021, followed by a more gradual decline, culminating in the 2028 projections: 2,249 children (scenario 2), 2,130 children (scenario 3), and 1,966 children (scenario 1). Breastfeeding promotion emerged as the most impactful intervention, accounting for over half of the total stunting cases averted under both Indonesia-wide and ENT-specific coverage scenarios. This was followed by interventions such as multiple micronutrient supplementation and vitamin A supplementation. The study highlights that reducing the prevalence of stunting among children requires a comprehensive prioritization of intervention strategies. The implementation of breastfeeding promotion, combined with appropriate complementary feeding practices, is expected to contribute significantly to achieving the sustainable development goal targets.